2008
DOI: 10.3928/01484834-20081201-06
|View full text |Cite
|
Sign up to set email alerts
|

Patient Simulator Sessions and Critical Thinking

Abstract: The project purpose was to determine whether measures of critical thinking show differences between three groups (simulator, non-simulator, control) of baccalaureate nursing students. The second purpose was to determine the moderating effect of students' preferred learning style. All groups experienced a moderate to large effect size in critical thinking scores. The corrected model for the total scale gain score was statistically significant but not significant for learning style or group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 29 publications
5
51
1
Order By: Relevance
“…The highest scores which reflected more of an analytical-intuitive mode of decision making process were obtained by students who had more experience in both role-play and discussion in debrief (mean = 70.5). These findings were reflected in previous studies which unanimously demonstrated the positive outcomes of increased HF-HPSMs exposure on critical thinking skills [21][22][23][24] . The lowest scoring which reflected an analytical skill tended to be attributed to the lack of the two experiences (mean = 63.6).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The highest scores which reflected more of an analytical-intuitive mode of decision making process were obtained by students who had more experience in both role-play and discussion in debrief (mean = 70.5). These findings were reflected in previous studies which unanimously demonstrated the positive outcomes of increased HF-HPSMs exposure on critical thinking skills [21][22][23][24] . The lowest scoring which reflected an analytical skill tended to be attributed to the lack of the two experiences (mean = 63.6).…”
Section: Discussionsupporting
confidence: 59%
“…As evidenced, more studies began to use critical thinking skills interchangeably with the decision making process to evaluate the effects of HF-HPSMs [21][22][23][24] . While that was the case, many other research studies concentrated on the development of critical thinking skills [25][26][27][28] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…e l s e v i e r . c o m / n e d t been suggested as a means of improving CT skills (Ravert, 2008;Sullivan-Mann et al, 2009), this remains unsubstantiated as findings among studies are not congruent and many relied on student or faculty perceptions of CT (Cant and Cooper, 2009). The ability of a nurse to critically think is a common theme in nursing programs (Forsberg et al, 2011).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…[6][7][8] Studies also indicate that with simulation students have increased critical thinking skills. [9][10][11] Despite common use and evidence to support its effectiveness, the use of simulation in health professions education remains controversial. A meta-analysis conducted by Spence Laschinger [12] examined simulation among nursing, medicine, and rehabilitation therapy pre-licensure students and found that learners enjoy simulation and that it made learning easier.…”
Section: Simulationmentioning
confidence: 99%